2015
DOI: 10.4236/ars.2015.42013
|View full text |Cite
|
Sign up to set email alerts
|

A Synoptic Review on Deriving Bathymetry Information Using Remote Sensing Technologies: Models, Methods and Comparisons

Abstract: This paper discusses the bathymetric mapping technologies by means of satellite remote sensing (RS) with special emphasis on bathymetry derivation models, methods, accuracies, advantages, limitations, and comparisons. Traditionally, bathymetry can be mapped using echo sounding sounders. However, this method is constrained by its inefficiency in shallow waters and very high operating logistic costs. In comparison, RS technologies present efficient and cost-effective means of mapping bathymetry over remote and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 54 publications
0
51
0
5
Order By: Relevance
“…In the literature, we observed that several spatial interpolation techniques were used to generate the bathymetry data based on survey samples depth, topographic data, and remote sensing based data, respectively [18,[26][27][28][29]. Among those, sample depths collected at various reaches of the river have been widely used for river bathymetry generation and hydrodynamic studies [30,31].…”
Section: Gap Fillingmentioning
confidence: 99%
“…In the literature, we observed that several spatial interpolation techniques were used to generate the bathymetry data based on survey samples depth, topographic data, and remote sensing based data, respectively [18,[26][27][28][29]. Among those, sample depths collected at various reaches of the river have been widely used for river bathymetry generation and hydrodynamic studies [30,31].…”
Section: Gap Fillingmentioning
confidence: 99%
“…Dữ liệu", sử dụng phần mềm ArcGIS tính hiện hiệu chỉnh bức xạ các kênh B2 và B3 theo công thức (1) và (2). Sau đó tính ảnh tỷ số theo công thức (9) với đầu vào là hai kênh ảnh B2 và B3 đã được hiệu chỉnh bức xạ, tức là: AnhTS = ln(B2)/ln(B3).…”
Section: Xây Dựng Mô Hình Và đáNh Giá độ Chính Xác Mô Hìnhunclassified
“…Theo truyền thống, chủ yếu được thực hiện bằng phương pháp đo đạc trực tiếp sử dụng máy đo sâu hồi âm có khả năng tạo ra các điểm đo hoặc các trắc diện theo lát cắt có độ chính xác cao. Tuy nhiên, phương pháp này thường tốn kém, chịu ảnh hưởng của điều kiện khí hậu trên biển và cần phải tiếp xúc trực tiếp với các khu vực cần khảo sát, độ phân giải thời gian và không gian thấp [2]. Đối với các khu vực có điều kiện địa hình tự nhiên phức tạp không có sự sống hoặc các đảo đang tranh chấp có quân đội đồn trú tại nhiều căn cứ trên các đảo nhỏ và bãi đá ngầm, việc tiếp cận khu vực khảo sát gặp nhiều khó khăn.…”
unclassified
“…Methods based on electromagnetic radiations are limited to shallow waters because of light attenuation within the water column (Jawak et al, 2015). In theory, based on light penetration in coastal waters, depths down to 50 m could be retrieved (Speight and Henderson, 2010).…”
Section: Optical Remote Sensingmentioning
confidence: 99%
“…However, the practical limit varies with local sea conditions. A maximum of 30 m deep is usually achieved when local conditions are exceptionally good (Collet et al, 2000;Jawak et al, 2015), and most often a depth of 15 m is reported as being the performance limit of optical remote sensing for bathymetry retrieval (e.g. Stumpf et al, 2003).…”
Section: Optical Remote Sensingmentioning
confidence: 99%